Efetividade da fortificação da água com ferro e vitamina C na prevalência deanemia e no estado nutricional em crianças assistidas em creches de BeloHorizonte-MG - Daniela da Silva Rocha (2010)
Iron deficiency anemia is considered the most common nutritional deficiency in childhood, with high prevalence in children attending daycare. Due to that, the aim of the present study was to evaluate the effectiveness of fortification of drinking water with iron and vitamin C in the reduction of the anemia in children attending daycare centers in Belo Horizonte, as well as to identify the prevalence of anemia and thedeterminants of the same in that population. This is a longitudinal study of intervention in children attending in 24 daycare centers in the Sanitário East District of Belo Horizonte. We evaluated 380 children aged six to 74 months, of these 07 were excluded because they showed hemoglobin less than or equal to 9.0 g / dL and 55 did not participate in the second evaluation, a total of 318 children assessed before and at theend of the intervention. To study the identification of risk factors, it was evaluated only children under five years old (n= 312), the group with the highest risk for anemia. A questionnaire was applied to parents or responsible for the children, containing information socioeconomic, maternal and related to the children's health. Anthropometric measurements (weight and height) and fingerstick blood samplesoccurred in two periods: fortification before and after five months of the same. Children were considered as anemic with hemoglobin < 11.0 g / dl for the group aged 6 to 59 months, and values < 11.5 g/dL for those aged 60 to 74 months. Statistical analysis were performed with Epi-info 6.04 Software and Statistical Package for the Social Sciences (SPSS). Multivariate analysis was performed to evaluate the association between these variables and anemia. The total number of children evaluated before and after the fortification was 318, being 52.2% male, with average of 45.4±15.8 months. The prevalence of anemia decreased significantly from 29.3% before the fortification, to 7.9% at the end of the study (p< 0,001). Considering the prevalence by age group, a XI X reduction of 62.5%, 75% and 78.8% was found for children of 24 months, 24 to 48months and > 48 months, respectively. The hemoglobin median increased 10.2% (from 11,80g/dL to 13,0g/dL), with a significant increase in all age groups. There was improvement in height-for-age and weight-for-age, however, only the first measurement showed a significant difference. For the study of the risk factors of anemia, the prevalence of anemia in this population was 30.8%, and the prevalence was 71.1% inchildren aged 24 months. The risk factors of anemia were age 24 months (OR: 9.08 CI: 3.96 to 20.83), and height-for- age < -1 z score (OR: 2.1, CI: 1.20 to 3.62). The fortification of water with iron and vitamin C significantly reduced the prevalence of anemia in children attending daycare centers, as well as it improved the nutritional status of them, being considered an important strategy to control this nutritionaldeficiency.